Black BiVO4: Size tailored synthesis, rich oxygen vacancies, and sodium storage performance - Xu, Xiaosa; Xu, Youxun; Xu, Fei; Jiang, Guangshen; Jian, Jie; Yu, Huiwu; Zhang, Enming; Shchukin, Dmitry; Kaskel, Stefan; Wang, Hongqiang (Journal of Materials Chemistry A, 2020)
BiVO4 nanoparticles with tailored sizes and rich oxygen vacancies were facilely synthesized via pulsed laser irradiation of colloidal nanoparticles (PLICN). As anode materials for Na-ion batteries, the revolutionized sodium storage process found in sub-10 nm BiVO4 nanocrystals results in outstanding properties including extraordinary rate capability and remarkable cycling stability.
CRIS-Team Scopus Importer:2022-04-14